Halal tourism research in Indonesian context: a bibliometric analysis - Taufiq Kurniawan; Mohammad Fakhrul Islam; Md. Abu Issa Gazi; Md Billal Hossain (Discover Sustainability)
Abstract Halal tourism is a growing sector of tourism that has attracted considerable attention in recent years due to its potential for economic growth and the need to meet the demands of Muslim travelers. This study aims to provide a comprehensive overview of halal tourism research in Indonesia through the utilization of bibliometric approach. The study utilizes Scopus database to analyze the publication trends, co-authorship, and thematic analysis, as well as the future research directions on this field in the context of Indonesia spanning the years 2017 to 2024. The findings indicate that there is a disparity in the involvement of authors and affiliations from Indonesia in terms of publications. The results show consistent growth in Indonesian publications, but emphasize the need for better quality and global dissemination. Moreover, the findings suggest that Indonesia plays a key role in the development of tourism in Indonesia due to its Muslim population and integration of Islamic principles in education and tourism. These findings highlight the importance of understanding Muslims tourists’ behavior, political economy influences, and service quality in different regions of Indonesia, thereby informing policy-making, industry practices, and future research agendas in this field.